A methods engineering study on Inter-art Metalwood products, Inc. - Gammad, Bridget; Reyes, Ma. Criselda; Riel, Janary (Diliman, Quezon City College of Engineering, 2005)
Inter-Art Metalwood Products, Inc. manufactures furniture for homes, offices, and institutions using modern materials and proven technology. It employs competent labor force and technologically advanced machineries. Custom store fixtures and components for panel furniture like tabletops, doors and foil laminations are also done on orders. Known for its contemporary design, quality and reliability, the company has gained its foothold in the construction industry particularly among housing and condominium developers.The study is centered on methods improvement and on how ease in production could be attained. Methods documentation and analysis is done on actual plant visits employing various tools learned in the Methods Engineering class. The study addressed problems such as inefficient production flow process, risks on workers' health, ineffective workers if the supervisors are not around, disorganized layout of the factory, dusty or untidy work place, poor housekeeping, machines not systematically arranged, and improper storage of tools and equipment. It is the task of the group to come up with possible solutions to the aforementioned problems. Using the Kepner-Tregoe Approach to decision analysis, alternatives are weighed based on specific criteria for each problem, depending on its being a MUST or WANT. Results showed that the company needs to implement the use of personal protective equipment, industrial vacuum, and incentive plan for workers. There should also be specific area for raw materials and cabinets for tools and equipment. The chosen alternatives are subject for implementation, where the group suggested some means in attaining and implementing those alternatives. These plans are guides for the subject company, the Inter-Art Metalwood Products, Inc. so that the management and the workers may be able to implement the various changes brought about by the alternatives. Application of the tools learned in the methods analysis class is highly used in this project study. The group used and illustrated some points with the use of Methods Engineering tools so as to clearly and effectively discuss and show the real situation in the subject company.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Inter-Art Metal Wood Products; Furniture industry and trade; Systems analysis